Saving sorghum from sooty stripe in West Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Sooty stripe is a serious disease of sorghum. Caused by a fungus called Ramulispora sorghi, it is particularly severe in areas with 500-1000 mm average annual rainfall. Recent studies indicate that sooty stripe can cause grain losses of nearly 50%....